Methodologies and Challenges for CRISPR/Cas9 Mediated Genome Editing of the Mammalian Brain - Nishizono, Hirofumi; Yasuda, Ryohei; Laviv, Tal (Frontiers in Genome Editing, 2020)
Neurons and glia are highly polarized cells with extensive subcellular structures extending over large distances from their cell bodies. Previous research has revealed elaborate protein signaling complexes localized within intracellular compartments. Thus, exploring the function and the localization of endogenous proteins is vital to understanding the precise molecular mechanisms underlying the synapse, cellular, and circuit function. Recent advances in CRISPR/Cas9-based genome editing techniques have allowed researchers to rapidly develop transgenic animal models and perform single-cell level genome editing in the mammalian brain. Here, we introduce and comprehensively review the latest techniques for genome-editing in whole animals using fertilized eggs and methods for gene editing in specific neuronal populations in the adult or developing mammalian brain. Finally, we describe the advantages and disadvantages of each technique, as well as the challenges that lie ahead to advance the generation of methodologies for genome editing in the brain using the current CRISPR/Cas9 system.